Exposé : finest digital art in the known universe. - Snoswell, Mark, ....-; Teo, Leonard, ....-; Wade, Daniel, ....- (Mylor : Ballistic, 2005)
Exposé is the industry's first annual art book celebrating the creative talents of digital artists worldwide. It grew to be a global success receiving critical acclaim from all quarters of the digital art industry. Selected by a panel of industry leaders *EXPOSÉ * showcases the finest digital artwork in the known universe.